2021
DOI: 10.1186/s12888-021-03422-9
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of cases of schizophrenia in the Malian population

Abstract: Background Schizophrenia is a relatively common disease worldwide with a point prevalence of around 5/1000 in the population. The aim of this present work was to assess the demographic, clinical, familial, and environmental factors associated with schizophrenia in Mali. Methods This was a prospective descriptive study on a series of 164 patients aged at least 12 years who came for a follow-up consultation at the psychiatry department of the Univers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…With nearly 30% of patients having consanguineous biological parents, the heritability of the risk variants was statistically verified. The study also revealed the history of 69% of patients with no cannabis use and 54% of patients who stayed abroad more than once in their lifetime (Coulibaly et al., 2021).…”
Section: Factors Affecting Schizophreniamentioning
confidence: 96%
See 2 more Smart Citations
“…With nearly 30% of patients having consanguineous biological parents, the heritability of the risk variants was statistically verified. The study also revealed the history of 69% of patients with no cannabis use and 54% of patients who stayed abroad more than once in their lifetime (Coulibaly et al., 2021).…”
Section: Factors Affecting Schizophreniamentioning
confidence: 96%
“…Recently, Coulibaly et al. (2021) made an astounding revelation in their study on the Malian population in 2020 regarding the disorder frequency in both sexes. With the male population at a surprising 80.5% (132 out of 164) and females accounting for 19.5% (32 out of 164).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Також визначається, що сімейний стан, професійні навички, фізичні вправи та соціальна підтримка впливали на якість життя пацієнтів з шизофренією [19]. Доведено, що початок шизофренії пов'язаний із соціально-демографічними, клінічними, генетичними та екологічними характеристиками [20].…”
Section: рисunclassified